Observation of the efficacy of long-term citrate anticoagulation in patients with maintenance hemodialysis - ZHUANG Feng; BI Xiao; DING Feng (Linchuang shenzangbing zazhi)
Objective To explore the effectiveness and safety of long-term citrate anticoagulant therapy in maintenance hemodialysis patients.Methods Twenty-six patients with high-risk bleeding tendency who underwent hemodialysis in the blood purification room of Shanghai Ninth People’s Hospital from January 2016 to December 2019 were selected,and all of them were treated with citrate anticoagulation for more than 3 months.We observed the clinical symptoms,adverse reactions and blood coagulation in the filter and pipeline during the treatment.The changes of coagulation indexes,electrolytes（blood sodium,potassium,chlorine,calcium,magnesium） and related biochemical indexes（parathyroid hormone,alkaline phosphatase,lipoprotein） were measured regularly before and after dialysis.We also analyzed the changes of bone metabolism in patients before and after citrate anticoagulant therapy.Results The patient had a good tolerance to citric acid anticoagulation and no serious complications occurred.In a total of 1 612 cases of hemodialysis,all treatments were not interrupted due to coagulation in the filter or pipeline.The filters were found to have only grade 2 blood clotting after the end of dialysis in 11 times of dialysis,and the total anticoagulant effectiveness reached 99.31%.Only 3.72% of the dialysis cases in the venous kettle were founded a few blood clots after dialysis which accounted for 3.72%（60/1 612）.There were no significant changes in blood coagulation function（PT,APTT）,serum sodium,magnesium,free calcium and total calcium before and after single dialysis（P>0.05）;but serum creatinine and potassium decreased significantly,while chlorine and HCO-3 increased（P<0.05）.There was no significant difference in the changes of calcium,parathyroid hormone and alkaline phosphatase after 3 months and 6 months of dialysis（P>0.05）.Conclusions Citrate anticoagulation can be carried out in maintenance hemodialysis for a long time.It has good curative effect and high safety,and has a broad application prospect.